The civil engineer and urban regeneration the fourth congress of civil engineers : introductory notes : Birmingham 28 September - 1 October 1988. (Thomas Telford, 1988)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of fourth congress of civil engineers held in Birmingham in 1988.